Vital Signs Strongly Predict Massive Transfusion Need in Geriatric Trauma Patients. Issue 7 (July 2016) - Fligor, Scott C.; Hamill, Mark E.; Love, Katie M.; Collier, Bryan R.; Lollar, Dan; Bradburn, Eric H.
Early recognition of massive transfusion (MT) requirement in geriatric trauma patients presents a challenge, as older patients present with vital signs outside of traditional thresholds for hypotension and tachycardia. Although many systems exist to predict MT need in trauma patients, none have specifically evaluated the geriatric population. We sought to evaluate the predictive value of presenting vital signs in geriatric trauma patients for prediction of MT. We retrospectively reviewed geriatric trauma patients presenting to our Level I trauma center from 2010 to 2013 requiring full trauma team activation. The area under the receiver operating characteristic curve was calculated to assess discrimination of arrival vital signs for MT prediction. Ideal cutoffs with high sensitivity and specificity were identified. A total of 194 patients with complete data were analyzed. Of these, 16 patients received MT. There was no difference between the MT and non-MT groups in sex, age, or mechanism. Systolic blood pressure, pulse pressure, diastolic blood pressure, and shock index all were strongly predictive of MT need. Interestingly, we found that heart rate does not predict MT. MT in geriatric trauma patients can be reliably and simply predicted by arrival vital signs. Heart rate may not reflect serious hemorrhage in this population.